Broadcast Production Workshops for Climate Change: iBroadkas Mo! Campaign Phase 2 - Philippine Federation of Rural Broadcasters (2018)
Together with the Philippine Federation of Rural Broadcasters (PFRB), CCAFS Southeast Asia launched the "Climate Change: iBroadkas Mo!" Phase 2 to to educate farmers about climate change through the radio. These reports document the three media workshops organized in Luzon (Echague, Isabela), Visayas (Baybay, Leyte), and Mindanao (Cagayan de Oro, Misamis Oriental) to educate media practitioners about climate change, to help them to write better stories about the issue.